Analisisi Unjuk Mesin Genset Kerja dengan Bahan Bakar Kombinasi Biogas dan LPG - Tino Hermanto; Muhammad Idris; Indra Hermawan; Akhiruddin Akhiruddin (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2022)
Energy has a very important role in supporting sustainable development because increasing development growth results in an increase in the need for fuel. In the performance of the generator engine, there are several important parameters in data collection such as effective power, torque, specific fuel consumption, and thermal efficiency. In this research, several types of fuels such as LPG and biogas are used, which are expected to be used as alternative fuels that are more environmentally friendly. This research was carried out experimentally on a 4-stroke generator engine which has made changes to the oil-fueled carburetor to use gas fuel so that it can be used using LPG or biogas fuel and added additional components to the fuel inlet line such as a flow meter so that it can be used as fuel. varying the amount of fuel that enters the combustion chamber. In addition, this study also compares the effect of LPG fuel and a mixture of biogas with LPG on the performance of the resulting engine. The best overall test results were obtained using LPG fuel with an increase in Ne: 27.31%, Torque: 0.05%, SFC: 0.34%, and Thermal Efficiency: 4.09% compared to using a combination of Biogas and LPG fuel.